Depress Poverty and Impress Rural Development through MNREGA - Yadav, Hemant (Journal of Commerce and Trade, 2018)
The poverty alleviation programmes of the Ministry of Rural Development are designed to act as safety nets to the poor during the times of crisis even while addressing partly the multi dimensional poverty. A committee was constituted by the government of India for estimating poverty shows that approximately 38 percent of India's populations in poor. According to 2011 census, more than 75% of poor people are living in rural areas. Low productivity and unemployment are the main reason of rural poverty. In order to alleviate rural poverty by generating employment, government of India launched Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), 2005. The effect of MNREGS would be positive for these farm households if the community and individual works undertaken under the scheme help in productivity enhancement of agriculture. Field evidence needs to be systematically analyzed before drawing conclusions of the programme impact. However, the programme is not free from challenges. This paper tries to highlight the challenges being faced by Mawana Block of Meerut District of UP, India as well as working of this programme.